A novel UHF Minkowski fractal antenna for partial discharge detection. Issue 8 (August 2017) - Wang, Feng; Bin, Feng; Sun, Qiuqin; Fan, Jingmin; Liang, Fangwei; Xiao, Xuanyi
Abstract: A compact and wideband ultra‐high‐frequency antenna is developed in this work. Based on the Minkowski fractal geometry of the lateral boundaries of monopole and the upper boundary of ground plane, miniaturization is realized. Meanwhile, by optimizing the dimension of the semi‐elliptical part of monopole and the triangular notch of ground plane, the impedance bandwidth is enhanced. To confirm the performance of antenna, a series of experiments are conducted. The size and ratio bandwidth of antenna are compared with existing broadband ones. The proposed antenna with size of 0.3 λL × 0.25 λL covers the frequency ranging from 700 MHz to more than 3 GHz and possesses an average gain of 4.08 dBi.